(untitled) (Journal of Universal Science Research, 2023)
In this article, we have explained about semiconductors, their types and their properties with scientifically based results.Semiconductors are materials that have properties in between normal conductors (materials that allow electric current to pass, e.g. aluminium) and insulators (which block electric current, e.g. sulphur).Semiconductors fall into two broad categories. First, there are intrinsic semiconductors. These are composed of only one kind of material. Silicon and germanium are two examples. They are also called "undoped semiconductors" or "i-type semiconductors".